Efficacy and Safety of Empagliflozin on Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Zhang, Yuyuan; Liu, Xiaobo; Zhang, Huazhu; Wang, Xuechang (Frontiers in Endocrinology, 2022)
Objective: Recently, clinical trials have shown a connection between non-alcoholic fatty liver disease (NAFLD) and empagliflozin. This paper aimed at comprehensively assessing the effectiveness and security of empagliflozin in NAFLD patients. Methods: Pubmed, Embase, Web of Science, Cochrane Library, CNKI, CBM, Wan-Fang digital database, VIP, and WHO ICTRP were searched for randomized controlled trials (RCTs) about the role of empagliflozin in NAFLD from inception to November 2, 2021. For continuous date, we used values of standardized mean differences (SMD) to present. Results: A total of four articles involving 244 NAFLD patients were included. Compared with the control group, empagliflozin could significantly reduce body mass index (BMI) (WMD − 0.98 [ 95 % CI: − 1.87, − 0.10], p = 0.03), liver stiffness measurement(LSM) (WMD − 0.49 [ 95 % CI: − 0.93, − 0.06], p = 0.03), aspartate aminotransferase (AST) (WMD -3.10 [95% CI: -6.18, -0.02], p = 0.05), homeostasis model assessment of insulin resistance (HOMA-IR) (WMD-0.45 [95 % CI: -0.90,0.00], p = 0.05). Conclusions: Empagliflozin can improve Body Composition, insulin resistance, liver fibrosis, and decrease hepatic enzymes in patients with NAFLD. Empagliflozin emerges as a new option for treating patients with NAFLD, further researches shall know the efficacy and safety of empagliflozin in NAFLD.